Optimising Scar Management Intervention in the Case of a Head-and-Neck Burn for a Patient with a Learning Disability - Katie Spooner; Matthew Pilley; Liz Rose; Stephen Frost; Reena Agarwal (MDPI AG, 2024)
Scars following burns can often prove complex to manage, particularly when crossing joints or special areas such as the head and neck, due to contractures. This case report discusses the individualised care and rehabilitation provided to a burn patient with a learning disability. The patient suffered both full and partial thickness burns equating to a total body surface area (%TBSA) of 7% of the face, neck, and anterior chest via the self-ignition of clothing. Acute treatment was provided at a regional burn unit followed by further in-patient care and rehabilitation at our burn facility. A motion rehabilitation instrument was employed to manage potential orofacial contracture; however, due to the patient's impaired social functioning, this device was found to be unsuitable. Subsequently, a bespoke mouth-opening device replicating an ice lolly was fabricated utilising computer-aided design (CAD), enhancing the patient's understanding along with encouraging independence. Microstomia was a risk in this case; however, this was prevented via the discussed regime, and successful patient rehabilitation was achieved.